The Importance of Traditional Outdoor Games in Children's Cognitive and Social Development - Raval, Rekha N. (Integrated Journal for Research in Arts and Humanities, 2023)
Play builds imagination and creativity in children. Play is essential to promote cognitive growth and healthy brain development of a child. Unstructured play helps develop a child's brain in a positive way. Through play, a child learns, solves problems, has fun and builds self confidence. Play delivers long- and short-term emotional and behavioural benefits in children. Play can help reduce anxiety, stress and irritability in children, as well as increase happiness and self-esteem. Play improves literacy. Through play, children learn about communication. Concentration games develop the ability to observe and maintain focus. Research shows that tired or bored children pay more attention to their work after a play break. Play encourages greater independence as well as allows experimentation with creativity and innovative ideas. Children need intellectual as well as physical play. Play promotes physical fitness and makes children physically strong. Traditional outdoor games play an important role in children's cognitive and social development. Traditional outdoor games provide a unique and enriching way for children to interact with each other, developing their cognitive and social skills. But nowadays traditional outdoor games are unknown and not even played by children. The research paper discusses the importance and effects of play, especially traditional outdoor games, in children's cognitive and social development.